Orthopedic information management system (OIMS) - Nurul Rasheedah Fateen, Ramli (2011)
Hospital management system has been developed over the past decades with the objective of streamlining the treatment flow of their patient while optimizing the doctors and staff performance ability.However,previous research on hospital management system shows a lacking in providing information especially to the public society. The need for strengthening this system is crucial as public have their own right to know and be included in the management.Therefore,hospital management has added an element of information in the system to include not only the doctors and hospital staff,but also the patients as the visitors of the hospital itself to access the system. This paper was made to specify the hospital management information system to a specific department that is Orthopedic Department to visualize the effectiveness of the system.Information on the latest news, promotion package offered by the hospital as well as direct line contact number of department of interest can be easily attained.